2019
DOI: 10.1523/jneurosci.3181-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the Perirhinal Cortex and Hippocampus During Discriminative Learning of Similar Objects

Abstract: Discriminative learning is a paradigm that has been used in animal studies, in which memory of a stimulus is enhanced when it is presented with a similar stimulus rather than with a different one. Human studies have shown that through discriminative learning of similar objects, both item memory and contextual memories are enhanced. However, the underlying neural mechanisms for it are unclear. The hippocampus and perirhinal cortex (PRC) are two possible regions involved in discriminating similar stimuli and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…This cross-domain role of the PrC suggests that discriminative and mnemonic factors might interact during encoding. In line with this assumption, Chen, Zhou, and Yang (2019) The role of anterior and medial temporal lobe structures in learning by means of fast mapping 6 found that the increased activation of the PrC during the discrimination between two highly similar items at encoding, compared to the discrimination between items from different categories, was predictive of later item recognition memory. Supportive evidence comes from an eye-tracking study by Zhou, Chen, and Yang (2018), who found that more saccades between similar items were also predictive of subsequent item memory.…”
Section: Introductionmentioning
confidence: 86%
“…This cross-domain role of the PrC suggests that discriminative and mnemonic factors might interact during encoding. In line with this assumption, Chen, Zhou, and Yang (2019) The role of anterior and medial temporal lobe structures in learning by means of fast mapping 6 found that the increased activation of the PrC during the discrimination between two highly similar items at encoding, compared to the discrimination between items from different categories, was predictive of later item recognition memory. Supportive evidence comes from an eye-tracking study by Zhou, Chen, and Yang (2018), who found that more saccades between similar items were also predictive of subsequent item memory.…”
Section: Introductionmentioning
confidence: 86%
“…One for most dissimilar, five for most similar). As one concept triplet had three similar pictures, three similarity rating scores for every two pictures of a triplet were acquired and averaged as one similarity score for each concept (Zhou et al, 2018;Chen et al, 2019). The naming accuracy for the pictures was 0.91 ± 0.12, the familiarity score was 1.81 ± 0.33, and the similarity score was 2.93 ± 0.51.…”
Section: Methodsmentioning
confidence: 99%
“…All triplets were first randomly assigned to four groups (Groups A-D), with one group used for the "same" condition, one for the "similar" condition, and the other two for the "different" condition (Chen et al, 2019). Next, each group was assigned to three different sets (S1, S2, and S3) for three retention intervals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations